Feasibility of the Ethno Social Learning Model for Elementary Children - Hamimah; Chandra; Yesi Anita; Annisa Kharisma (Universitas Pendidikan Ganesha, 2022)
Local cultural wisdom needs to be maintained because it indicates the characteristics of a region, including the social field. The social culture of each region is very unique and different. The uniqueness of social culture in each region always adheres to positive teachings and deserves to be preserved. The purpose of this research is to produce an ethnosocial learning model that is suitable for use in the learning process. The research was conducted with an R&D approach. The research subjects were students, teachers, and principals of elementary schools. The instrument used is a questionnaire. The results showed that elementary school ethnosocial involvement in the social science learning process was shallow. In fact, what often happens is to provide examples of socio-culture in other areas of learning in elementary schools. This incident occurred without any intentional element and was in accordance with what was thought when the social science learning process took place. For this reason, it is necessary to create an ethnosocial learning model so that there is an effort to pay attention to ethnosocial in their own environment. One of the efforts that can be done is to develop an ethnosocial learning model in elementary schools. The ethnosocial learning model that was created was declared feasible to be applied in elementary schools. The advantage of the ethnosocial learning model is that this model pays attention to the social development of children which is adapted to the local culture.